Change in the Treg/Th17 cell imbalance in hepatocellular carcinoma patients and its clinical value. Issue 32 (August 2017) - Lan, Yong-Ting; Fan, Xiao-Peng; Fan, Yu-Chen; Zhao, Jing; Wang, Kai
Abstract : Abstract: Recent studies have indicated that the T cell mediated immune response plays an important role in the pathogenesis of hepatitis B virus-associated hepatocellular carcinoma (HCC), but the underlying mechanism remains unclear. In this study, we found an imbalance in Treg/Th17 cells in peripheral blood mononuclear cells from HCC patients. The percentages of CD4 + CD25 + FOXP3 + Treg cells and CD4 + IL-17 + Th17 cells were significantly higher in HCC patients than in the controls. The numbers of Treg and Th17 cells were increased and correlated in a positive linear manner. Moreover, the increased percentages of Treg and Th17 cells were closely related to the tumor stage and tumor size of HCC. Therefore, we concluded that Treg and Th17 cells might participate in the promotion of the invasion and progression of HCC and that a Treg/Th17 cell imbalance might be able to serve as an important indicator for determining the progression and prognosis of HCC. Further studies might provide novel therapeutic targets for HCC.